2019
DOI: 10.1021/acs.chemrestox.9b00230
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroxyacetone Exposure Alters NAD(P)H and Induces Mitochondrial Stress and Autophagy in HEK293T Cells

Abstract: Dihydroxyacetone phosphate (DHAP) is the endogenous byproduct of fructose metabolism. Excess DHAP in cells can induce advanced glycation end products and oxidative stress. Dihydroxyacetone (DHA) is the triose precursor to DHAP. DHA is used as the active ingredient in sunless tanning products, including aerosolized spray tans, and is formed by the combustion of solvents found in electronic cigarettes. Human exposure to DHA has been increasing as the popularity of sunless tanning products and electronic cigarett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…93 Although hydroxycarbonyls are abundant in e-cigarette aerosols, a general lack of toxicological data precludes health risk assessment. Smith et al 94 found that exogenous exposure to dihydroxyacetone is cytotoxic and will cause cell death by apoptosis. Glycolaldehyde is also suspected to have biological toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…93 Although hydroxycarbonyls are abundant in e-cigarette aerosols, a general lack of toxicological data precludes health risk assessment. Smith et al 94 found that exogenous exposure to dihydroxyacetone is cytotoxic and will cause cell death by apoptosis. Glycolaldehyde is also suspected to have biological toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Several avenues for research are worth exploring. For instance, translational studies on the precise cellular mechanisms involved in EVC toxicity are needed, exploring for instance microRNA, inflammatory cascade, autophagy, apoptosis, and regeneration [36][37][38]. Observational studies on large samples are needed to accurately gauge the short and long-term risks of EVC in apparently healthy subjects and in patients with cardiovascular disease [39].…”
Section: Discussionmentioning
confidence: 99%
“…NAD(P)H levels were measured using the endogenous autofluorescence of these dinucleotides when they are excited with a 355 nm laser, as described in [ 34 ]. Briefly, HEK293T and HepG3 cells were seeded in an 8-well chambered coverglass at a density of 2 X 10 4 cells/chamber and 4 X 10 4 cells/chamber, respectively and incubated ON at 37°C in a 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%